Statistical Inference for the Epanechnikov-Burr XII Distribution with Simulation and Case Studies (European Journal of Pure and Applied Mathematics, 2025)
In this article, the Epanechnikov kernel function and the Burr-XII distribution are combined to create the Epanechnikov-Burr-XII distribution (EBD). The mathematical characteristics of this novel distribution, such as moments, moment generating function, reliability analysis functions, and order statistics, are investigated. The maximum likelihood estimation (MLE) approach is used to estimate the EBD's parameters. The consistency of the MLE estimators is demonstrated by a simulation analysis, and real-world data applications reveal that the EBD fits data better than the conventional Burr-XII distribution. The outcomes demonstrate how adaptable and useful the EBD is for modeling lifespan data.
Keywords: Burr XII Distribution, Epanechnikov, maximum likelihood, moment, moment generating function.